2012
DOI: 10.1590/s1516-35982012000400013
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and insulin in the seminal plasma of zebu bulls in peripuberty

Abstract: -In order to determine the profile of leptin and insulin values in seminal plasma and their correlations with sperm patterns during the peripuberty, a total of 16 crossbred Gyr dairy bulls were monitored from 60 days before to 60 days after puberty, separated into two groups, early and regular, according to the onset of puberty. Hormone values were determined by radioimmunoassay after gel filtration in fast performance liquid chromatography and semen patterns,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…In the present study, it was observed a higher percentage of cells with the intact plasma membrane, intact acrosome, and high mitochondrial membrane potential (PIAIHP) when insulin (150 µUI/mL) was added to both extenders. Such responses to the insulin action can be assured, since the plasma membrane, acrosomal and metabolism are cytological targets (Souza et al, 2012). During semen cryopreservation, between 15º to 5º C, mostly membranes alterations occur, such as rupture and loss in the phospholipid arrangements.…”
Section: Pimentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, it was observed a higher percentage of cells with the intact plasma membrane, intact acrosome, and high mitochondrial membrane potential (PIAIHP) when insulin (150 µUI/mL) was added to both extenders. Such responses to the insulin action can be assured, since the plasma membrane, acrosomal and metabolism are cytological targets (Souza et al, 2012). During semen cryopreservation, between 15º to 5º C, mostly membranes alterations occur, such as rupture and loss in the phospholipid arrangements.…”
Section: Pimentioning
confidence: 99%
“…The addition of IGF-I and insulin combined did not improve sperm quality after thawing in both Triladyl ® and Botubov ® extenders. It was expected that the association of these hormones would guarantee better cell preservation, as IGF-I acted on sperm motility and linear speed, through the connection with receptors present in sperm, and that insulin acted on metabolism (Souza et al, 2012). The associated groups showed a lower percentage of sperm motility and a lower number of intact cells.…”
Section: Pimentioning
confidence: 99%
“…As a pleiotropic molecule, leptin exhibits both positive and negative influences on sperm quality ( Andò & Aquila, 2005 ; Leisegang et al, 2014 ; Xin et al, 2019 ). The evidence has indicated considerable differences as to the concentrations of leptin in seminal plasma of different species ( Lackey, Gray & Henricks, 2002 ; Guo et al, 2014 ; Elfassy et al, 2018 ; El-Maaty et al, 2014 ; Kumar et al, 2016 ; SouzaI et al, 2012 ), the physiological implications of these differences in seminal plasma have not been clarified.…”
Section: Introductionmentioning
confidence: 99%